HRM 4.0 and New Managerial Competences Profile: The COMAU Case - Fregnan, Ezio; Ivaldi, Silvia; Scaratti, Giuseppe (Frontiers in Psychology, 2020)
The digital revolution has generated huge changes in the world of work, with relevant implications for the Human Resources Management (HRM) function. New challenges arise in facing digital work, digital employees, and digital management, such that the connection between new technologies and HRM is now described as electronic HRM (e-HRM). Challenges and connection entail the possibility to review the notion of HRM itself, examining new research perspectives and lines of interpretation following a Critical Management Studies approach, thus developing a more contextualized view in conceiving HRM, a more expansive consideration of stakeholders, and a longer-term perspective in approaching the results of digital transformation and HRM outcomes. The article analyzes a specific organizational case, involving a multinational enterprise, and explores how the case study enhances the understanding of HRM as a social practice embedded in specific situated contexts. Such a conception enables the engagement of multiple rationalities, related to both internal and external stakeholders, overcoming a “mere antiperformance stance” and achieving forms of reconstructive reflexivity concerning the interconnection between the digital age, HRM, and the innovative generation of social value through an authentic corporate responsibility.